Penerapan Konsep Sense Of Place Pada Akomodasi Glamping Di Kintamani: Bahasa Indonesia - I Komang Diyo Pramana Putra; I Ketut Sugihantara; I Wayan Wirya Sastrawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
Seeing the importance of accommodation in the scope of tourism, glamping is one of the very supportive accommodations, especially in Kintamani by being an accommodation that is easily accessible to all levels of society, can elevate the local architecture of Kintamni, and is able to become a sustainable accommodation both in the social, cultural, economic fields. , as well as the environment. However, from several glamping that already exist in Kintamani, there are still a few glamping that promote and introduce glamping in a local context, especially in terms of sustainable local Kintamani architecture. Therefore, this research was conducted to ensure that the design of glamping located in Kintamani is expected to provide an example of using nature to become a tourist accommodation that always pays attention to the surrounding environment, is sustainable in terms of natural, social, cultural and economic aspects, and is capable of introducing a glamping accommodation with the architectural context of the Kintamani locality itself so that local elements in the area are better known, not faded